2016
DOI: 10.1016/j.psyneuen.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–pituitary–adrenal axis response to acute psychosocial stress: Effects of biological sex and circulating sex hormones

Abstract: Summary Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis influences the risk for developing stress-related disorders. Sex-dependent differences in the HPA axis stress response are believed to contribute to the different prevalence rates of stress-related disorders found in men and women. However, studies examining the HPA axis stress response have shown mixed support for sex differences, and the role of endogenous sex hormones on HPA axis response has not been adequately examined in humans. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(131 citation statements)
references
References 81 publications
4
118
1
3
Order By: Relevance
“…This is in agreement with population studies and a number of clinical studies showing that men experienced greater HPA-axis activity than women in response to various laboratory stressors, including examination stress, pain, cognitive tasks, and public speaking (Stephens et al, 2016; Kirschbaum et al, 1992; Zimmer et al, 2003; Kirschbaum et al, 1999; Kudielka et al, 1998; Seeman et al, 2001). In this study, only women demonstrated reduced activity in mPFC and hypothalamic-hippocampal connectivity dependent on cortisol.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with population studies and a number of clinical studies showing that men experienced greater HPA-axis activity than women in response to various laboratory stressors, including examination stress, pain, cognitive tasks, and public speaking (Stephens et al, 2016; Kirschbaum et al, 1992; Zimmer et al, 2003; Kirschbaum et al, 1999; Kudielka et al, 1998; Seeman et al, 2001). In this study, only women demonstrated reduced activity in mPFC and hypothalamic-hippocampal connectivity dependent on cortisol.…”
Section: Discussionsupporting
confidence: 91%
“…A parsimonious explanation of this coupling is that participants found the TSST (or its modification) to invoke a challenge more than a stressor response. Robust coupling across axes fits with the emerging dual-axis models (Marceau et al, 2015; Susman, Peckins, Bowes, & Dorn, 2017; Harden et al, 2016; Juster, Raymond, Desrochers, Lupien, 2016; Stephens, Mahon, McCaul, & Wand, 2016), and with an interpretation of the TSST as both a stressor and a challenge (Mehta, Jones, & Josephs, 2008; Mehta, Welker, Zilioli, & Carre, 2015; Denson, Mehta, & Tan, 2013; Salvador, 2005). It is more difficult to integrate with models that describe inhibition of one axis by the other (Viau, 2002; Koob & LeMoal, 2001), such as studies which describe androgens as a stress buffer, DHEA as an anti-glucocorticoid (Kalimi et al, 1994), or which find unique high testosterone/cortisol reactivity ratio findings (Glenn et al, 2011; Huovinen et al, 2009; Welker et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…This pattern suggests that playing the hawk-dove game with another man may have caused men's cortisol and testosterone responses to resist circadian decline. This general pattern resembles sex differences in endocrine reactivity to social-evaluative stressors such as the Trier Social Stress Test (TSST); men tend to show stronger cortisol stress responses to the TSST compared to women (Stephens et al, 2016). The testosterone response pattern in men is also consistent with the challenge hypothesis (Wingfield et al, 1990;Archer, 2006).…”
Section: Hormones Behavior and Sex/gendermentioning
confidence: 56%